An attention and interpretation bias for illness-specific information in chronic fatigue syndrome. Issue 5 (29th November 2016) - Hughes, A. M.; Chalder, T.; Hirsch, C. R.; Moss-Morris, R.
Abstract : Background: Studies have shown that specific cognitions and behaviours play a role in maintaining chronic fatigue syndrome (CFS). However, little research has investigated illness-specific cognitive processing in CFS. This study investigated whether CFS participants had an attentional bias for CFS-related stimuli and a tendency to interpret ambiguous information in a somatic way. It also determined whether cognitive processing biases were associated with co-morbidity, attentional control or self-reported unhelpful cognitions and behaviours. Method: A total of 52 CFS and 51 healthy participants completed self-report measures of symptoms, disability, mood, cognitions and behaviours. Participants also completed three experimental tasks, two designed specifically to tap into CFS salient cognitions: (i) visual-probe task measuring attentional bias to illness (somatic symptoms and disability) v . neutral words; (ii) interpretive bias task measuring positive v . somatic interpretations of ambiguous information; and (iii) the Attention Network Test measuring general attentional control. Results: Compared with controls, CFS participants showed a significant attentional bias for fatigue-related words and were significantly more likely to interpret ambiguous information in a somatic way, controlling for depression and anxiety. CFS participants had significantly poorer attentional control than healthy individuals. Attention and interpretation biases were associated with fear/avoidance beliefs. Somatic interpretations were also associated with all-or-nothing behaviour and catastrophizing. Conclusions: People with CFS have illness-specific biases which may play a part in maintaining symptoms by reinforcing unhelpful illness beliefs and behaviours. Enhancing adaptive processing, such as positive interpretation biases and more flexible attention allocation, may provide beneficial intervention targets.